2015
DOI: 10.1038/npp.2015.280
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Glutamatergic Synaptic Plasticity in the Hippocampal CA1 Field of Food-Restricted Rats: Involvement of CB1 Receptors

Abstract: The endogenous endocannabinoid system has a crucial role in regulating appetite and feeding behavior in mammals, as well as working memory and reward mechanisms. In order to elucidate the possible role of cannabinoid type-1 receptors (CB1Rs) in the regulation of hippocampal plasticity in animals exposed to food restriction (FR), we limited the availability of food to a 2-h daily period for 3 weeks in Sprague-Dawley rats. FR rats showed a higher long-term potentiation at hippocampal CA1 excitatory synapses with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
(51 reference statements)
0
14
0
5
Order By: Relevance
“…Rats or mice that run or are fasted intermittently exhibit enhanced LTP at hippocampal synapses compared with sedentary animals fed ad libitum 2729 . Daily TRF (22 hours of fasting every day) for 3 weeks improves performance in the Barnes maze test and increases dendritic spine density and LTP in CA1 neurons in rats 30 . IMS can also prevent age-related deficits in LTP 31,32 .…”
Section: Neuronal Adaptations To Imsmentioning
confidence: 95%
“…Rats or mice that run or are fasted intermittently exhibit enhanced LTP at hippocampal synapses compared with sedentary animals fed ad libitum 2729 . Daily TRF (22 hours of fasting every day) for 3 weeks improves performance in the Barnes maze test and increases dendritic spine density and LTP in CA1 neurons in rats 30 . IMS can also prevent age-related deficits in LTP 31,32 .…”
Section: Neuronal Adaptations To Imsmentioning
confidence: 95%
“…A number of previous studies suggest that FR (DR/CR) may lead to alterations of hippocampus (Benau et al, 2014; Conrad, 2010), which further contribute to changes of memory (Partadiredja and Bedi, 2011). For example, FR altered hippocampal CB1R expression and function in rats (Talani et al, 2016), and CR enhanced hippocampal neurogenesis and remote contextual fear memory in adult mice (Hornsby et al, 2016). Regarding the developing phase, it was published recently that young‐onset CR could result in alterations of neurogenesis in the dentate gyrus, which may explain some impairment of spatial cognition (Cardoso et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, in non-stressed rats, CB 1 activation reduced the excitatory post-synaptic currents. In addition, Talani et al ( 2016 ) mimicked the effects of food restriction on glutamate release, LTP induction, and BDNF release in the hippocampus, by blocking CB 1 receptors. Hu et al ( 2011 ) showed that rats exposed to chronic restraint stress presented an impaired endocannabinoid-mediated DSI in the CA 1 pyramidal neurons of the dorsal hippocampus.…”
Section: Stress Induces Changes In Cannabinoid-mediated Hippocampal Nmentioning
confidence: 99%